EFEKTIFITAS PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING DENGAN CONTEXT-RICH PROBLEMS PADA MATERI POKOK TERMOKIMIA DALAM MENINGKATKAN HASIL BELAJAR SISWA DAN KEMAMPUAN BERPIKIR KRITIS - Khaeruman, Khaeruman; Nurhidayati, Siti Nurhidayati; Rahayu, Sari (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2014)
Passive learning leads to low student chemistry learning outcomes. This study aims to improve learning outcomes and students' critical thinking skills on thermochemical subject matter through problem-solving learning model with context-rich problems. This research was conducted in 2 cycles, namely: planning, implementation, observation, evaluation, and reflection. Student learning result data obtained through formative test given at each end of the cycle and students' critical thinking skills adapted to the indicator of critical thinking. Learning outcomes show that classical completeness earns a score of at least 70 85% of the total number of students taking the evaluation test. The results showed that the results of classical evaluation in cycles I and II were 35% and 90%, respectively. Improvement of learning result that is 157%, and critical thinking ability of student in cycle I score that is 45% (uncritical category). In cycle II, the score achieved is 65% (critical category). Increased critical thinking ability reached 44.4%. We conclude that the application of problem-solving learning model with Context-rich problems can improve learning outcomes and critical thinking skills